2017
DOI: 10.29313/gmhc.v5i1.2097
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Kadar Gula Darah Akibat Pemberian Ekstrak Manggis (<i>Garcinia mangostana</i>) dan Tomat (<i>Lycopersicum esculentum Mill</i>) pada Tikus Diabetes

Abstract: AbstrakMasyarakat percaya bahwa kulit manggis dan tomat dapat menurunkan kadar gula darah dan bermanfaat sebagai antidiabetes, namun hal ini perlu diuji untuk menemukan bukti ilmiahnya. Tujuan penelitian ini adalah menganalisis efek penurunan kadar gula darah akibat pemberian kombinasi ekstrak kulit manggis (Garcinia mangostana) dengan tomat (Lycopersicum esculentum Mill) pada tikus putih (Rattus norvegicus) Wistar diabetes. Penelitian ini menggunakan rancangan pretest-posttest with control group design. Ekstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Research conducted by Astuti and R (2018) revealed that provision of tomato juice to blood glucose levels in pre-diabetes as much as 200 ml for 21 days showed a decrease in blood glucose by 9.00 mg/dl 2 . Another research conducted by Yusni (2015) showed that the administration of tomato extract and mangosteen extract to diabetic mice each 50 mg/kg bb/day for seven days showed a decrease in blood glucose levels by 56.67% 7 . Research by Chairunnisa (2012) was conducted by giving tomato paste to diabetic mice as much as 62 mg for 7 days reduced blood glucose levels by 262 mg/dl with a decreasing percentage reaching 75.60% 8 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research conducted by Astuti and R (2018) revealed that provision of tomato juice to blood glucose levels in pre-diabetes as much as 200 ml for 21 days showed a decrease in blood glucose by 9.00 mg/dl 2 . Another research conducted by Yusni (2015) showed that the administration of tomato extract and mangosteen extract to diabetic mice each 50 mg/kg bb/day for seven days showed a decrease in blood glucose levels by 56.67% 7 . Research by Chairunnisa (2012) was conducted by giving tomato paste to diabetic mice as much as 62 mg for 7 days reduced blood glucose levels by 262 mg/dl with a decreasing percentage reaching 75.60% 8 .…”
Section: Discussionmentioning
confidence: 98%
“…Lycopene binds to reactive oxygen and increases antioxidant potency, thereby reducing oxidative damage to lipids. Meanwhile, the non-oxidative mechanism of lycopene is done through gene function which improves gap-junction communication, hormone modulation, and immune response, all of which can reduce degenerative diseases such as DM 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease follows this damage in insulin secretion, which results in the reaction of glycogenesis and reduced glucose transport in cells. In addition, glycogenolysis becomes uncontrolled, resulting in increased blood glucose in the body (Yusni et al 2017). Meanwhile, according to Sari et al (2020), alloxan is a toxic glucose analog that selectively destroys insulinproducing pancreatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…(Wulandari, 2014) menyatakan hasil penelitiannya bahwa rata-rata kadar gula darah sebelum mengkonsumsi jus kulit buah manggis 210,9 mg/dl dan rata- rata setelah mengkonsumsi jus buah manggis sebesar 169,9 mg/dl. (Yusni, Akbar, Rezania, & Fahlevi, 2017) menyatakan bahwa pemberian ekstrak kulit manggis dan tomat dengan dosis 50mg/kg BB/hari masingmasing menurunkan kadar glukosa darah bagi diabetes. (Kurniawati, 2014) menyatakan bahwa xanton dalam jus kulit buah manggis dapat menghambat aktivitas enzim glukosidae sebesar 64,71% pada penderita diabetes.…”
Section: Hasil Penelitian Dan Pembahasan a Hasilunclassified